Estimated medical cost reductions associated with use of novel oral anticoagulants vs warfarin in a real-world non-valvular atrial fibrillation patient population. (26th August 2014) - Amin, Alpesh; Stokes, Michael; Makenbaeva, Dinara; Wiederkehr, Daniel; Wu, Ning; Lawrence, John H.
Abstract: Objective: Results of randomized clinical trials (RCT) demonstrate that novel oral anticoagulants (NOAC) are effective therapies for reducing the risk of stroke in non-valvular atrial fibrillation (NVAF). Prior medical cost avoidance studies have used warfarin event rates from RCTs, which may differ from patients receiving treatment in a real-world (RW) setting, where the quality of care may not be the same as in a RCT. The purpose of this study was to estimate the change in medical costs related to stroke and major bleeding for each NOAC (apixaban, dabigatran, and rivoraxaban) relative to warfarin in a RW NVAF population. Methods: Patients ( n  = 23, 525) with a diagnosis of NVAF during 2007–2010 were selected from a Medco population of US health plans. Stroke and major bleeding excluding intracranial hemorrhage (MBEIH) events were identified using diagnosis codes on medical claims. RW reference event rates were calculated during periods of warfarin exposure. RW event rates for NOACs were estimated by multiplying the corresponding relative risk (RR) from the RCTs by each reference rate. Absolute risk reductions (ARR) or number of events avoided per patient year were then estimated. Changes in medical costs associated with each NOAC were calculated by applying the ARR to the 1-year cost for each event. Costs for stroke and MBEIH were obtained from the literature. Drug and international normalized ratio monitoring costs were not considered in this analysis. Results: Compared to RW warfarin, use of apixaban and dabigatran resulted in total (stroke plus MBEIH) medical cost reductions of $1245 and $555, respectively, during a patient year. Rivaroxaban resulted in a medical cost increase of $144. Conclusions: If relative risk reductions demonstrated in RCTs persist in a RW setting, apixaban would confer the greatest medical cost savings vs warfarin, resulting from significantly lower rates of both stroke and MBEIH.